Focus Group Discussions E-Learning based on Prior Knowledge and Problems in the Covid-19 Pandemic Period - Yunia Mulyani Azis,; Nurul Fatimah, (Technium Social Sciences Journal, 2020)
The Covid-19 pandemic forced many campuses around the world to close. In Indonesia, the closure of the campus began in mid-March 2020. The closure of the campus for a long time will harm students. To prevent this, the Indonesian government encourages campuses to hold online lectures or E-Learning. One of the campuses implementing E-Learning is STIE Ekuitas Bandung. The change from traditional lectures to E-Learning is not as easy as the theory. There are technological limitations, especially connections that cause students to have problems when forced to attend college in the form of video streaming. Besides, the economic recession caused by the pandemic is also another obstacle. On the other hand, most lecturers do not know how to give lectures effectively via the web, because they cannot get feedback from students. One solution we propose in this paper is to revive group discussions on school E-Learning sites. Using the student's Prior knowledge about E-Learning as a parameter, we conclude that the learning design provided in e-learning has to be slower compared to face-to-face learning with the aim that respondents have time to read, understand and finally understand with their efforts.